2014
DOI: 10.1063/1.4891963
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the responsivity characteristics of Au/ZnO/MgZnO and Au/MgZnO/ZnO structured ultraviolet photodetectors

Abstract: We report on the ultraviolet photodetectors based on the MgZnO/ZnO and ZnO/MgZnO double-layer films prepared by magnetron sputtering method. The spectral response shows only one responsivity peak in the 1.0 and 1.5 h photodetectors (denoted by the deposition time of one layer of the films) and two peaks in the 0.5 h photodetectors. To our surprise, the Au/MgZnO/ZnO photodetectors have larger responsivity than that of the Au/ZnO/MgZnO ones. A physical mechanism focused on depletion width is given to explain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Among highly performing materials, zinc oxide is a promising transparent metal oxide with a room temperature bandgap of 3.37 eV that matches well the lower edge of the visible light spectrum . Nano‐ and microstructured ZnO photodetectors have been produced by several methods such as RF magnetron sputtering, sol‐gel, chemical vapor deposition, and pulsed laser deposition demonstrating significant improvement over bulk equivalents. Recently, Ji et al have demonstrated fabrication of flexible devices with up to 1.56 × 10 3 photo‐ ( I UV ) to dark‐current ( I dark ) ratio at a bias of 3 V by epitaxial growth of ZnO films on poly‐ethylene‐terephthalate (PET).…”
Section: Figures Of Merit Of State‐of‐the‐art Wide Bandgap Zno Photodmentioning
confidence: 99%
“…Among highly performing materials, zinc oxide is a promising transparent metal oxide with a room temperature bandgap of 3.37 eV that matches well the lower edge of the visible light spectrum . Nano‐ and microstructured ZnO photodetectors have been produced by several methods such as RF magnetron sputtering, sol‐gel, chemical vapor deposition, and pulsed laser deposition demonstrating significant improvement over bulk equivalents. Recently, Ji et al have demonstrated fabrication of flexible devices with up to 1.56 × 10 3 photo‐ ( I UV ) to dark‐current ( I dark ) ratio at a bias of 3 V by epitaxial growth of ZnO films on poly‐ethylene‐terephthalate (PET).…”
Section: Figures Of Merit Of State‐of‐the‐art Wide Bandgap Zno Photodmentioning
confidence: 99%
“…As compared to the MSM-PDs without the Mg x Zn 1-x O capping layer, the PDs with the Mg x Zn 1-x O/ZnO bi-layer presented higher dark current, photocurrent, and photoresponsivity due to the shielding of ambient oxygen, defect, and surface states passivation by the Mg x Zn 1-x O capping layer [21]. The Au/Mg x Zn 1-x O/ZnO PDs had larger responsivity than Au/ZnO/Mg x Zn 1-x O PDs [22]. By varying the applied bias voltage, the detection wavelength of the Mg x Zn 1-x O/ZnO MSM-PDs could be modulated from a single to a dual wavelength [23].…”
Section: Introductionmentioning
confidence: 89%
“…ZnO-based materials are attractive semiconductors for fabricating ultraviolet (UV) photodetectors, such as p-n, Schottkybarrier, and metal-semiconductor-metal structures, [1][2][3][4][5][6][7][8][9][10][11][12] due to the advantages of wide band gap (3.2 eV), high transparency (>80%) in the visible wavelength region, high exciton binding energy (60 meV), and non-toxicity. 13,14 The addition of a Mg atom in ZnO leads to the formation of Mg x Zn 1Àx O with a band gap tuneable from 3.2 to 7.8 eV.…”
Section: Introductionmentioning
confidence: 99%